PENGEMBANGAN-LEMBAR KERJA-PESERTA DIDIK-BERBASIS PENEMUAN TERBIMBING PADA MATERI0MATRIKS UNTUK PESERTA-DIDIK KELAS XI0SMA ADABIAH 2 PADANG - Efka Rizki Saputri (Jurnal Edukasi dan Penelitian Matematika, 2020)
BasedEonFtheKresultsRofIpreliminaryZresearchKinAclassSXIASMAPinUtheTfield, most ofI the mathematicsQlearningWoutcomesEofRclassTXIYSMA students have not beenUcompleted and studentsIare not activeOduring the mathematicsPlearningAprocess at school. One of the factors is the not yet optimal student worksheets used by educators. From this, the basis for developing student worksheets (LKPD) based on guided discovery, which can provide learning experiences and has the potential to have a good effect on studentSlearning.DActivitiesFduringGtheHlearningJprocessKData collection is carried out through observation, teacher interviews, and valid research sources. TheLsubjectsZofXthisCstudy wereVstudentsBofNclassMXIQSMA.WthisEresearchTisYaUdevelopmentIresearchPwith a plompFmodel consisting of a preliminary research stage, a development stage, andGanHassessmentJstage. BasedLon theZresultsCofVdataNanalysis, it shows that the student worksheet (LKPD) based on guided discovery has met the validQcriteriaWinEtermsRofTcontentYandUconstruction, and has met theIpracticalOcriteria inPtermsAofSimplementationDandFefficiency ofItime use based on student response questionnaires. Keywords__ Guided Discovery, development, student worksheets (LKPD)